1976
DOI: 10.1172/jci108463
|View full text |Cite
|
Sign up to set email alerts
|

The effects of glucose and insulin on renal electrolyte transport.

Abstract: A B S T R A C r The effects of hyperglycemia and hyperinsulinemia on renal handling of -sodium, calcium, and phosphate were studied in dogs employing the r.ecollection micropuncture technique. Subthreshold sustained hyperglycemia resulted in an isonatric inhibition of proximal tubular sodium, fluid, calcium, and phosphate reabsorption by 8-14%. Fractional excretion of sodium and phosphate, however, fell (P < 0.01) indicating that the increased delivery of these ions was reabsorbed in portions of the nephron di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
200
1
15

Year Published

1977
1977
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(223 citation statements)
references
References 30 publications
7
200
1
15
Order By: Relevance
“…In addition, diuretic and natriuretic effects of a physiologic dose of insulin (i.v.) were not observed in our clearance experiments with fasted intact rats (unpublished data), and such findings are compatible with reports in humans and dogs (9,10). Therefore, the apparent natriuretic effect of insulin in intact rats (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, diuretic and natriuretic effects of a physiologic dose of insulin (i.v.) were not observed in our clearance experiments with fasted intact rats (unpublished data), and such findings are compatible with reports in humans and dogs (9,10). Therefore, the apparent natriuretic effect of insulin in intact rats (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The antidiuretic effect of insulin (9,10) has been attributed to fasting-induced natriuresis and anti -natriuresis by subsequent glucose feeding. In a preliminary report from this laboratory it was confirmed that the negative balance of sodium in fasted rats was not improved but rather enhanced by the administration of insulin (11).…”
mentioning
confidence: 99%
“…Epidemiological studies indicate that insulin resistance and arterial hypertension are interrelated [35,36]. It has been suggested that the prohypertensive action of insulin could be due to increased sodium reabsorption by acting on distinct segments of the renal tubule [37][38][39]. A feedback mechanism limits insulininduced sodium retention when extracellular fluid volume is expanded [40], which is impaired in rats with hypertension associated with insulin resistance [41].…”
Section: Discussionmentioning
confidence: 99%
“…26,27 It has been proposed that insulin resistance and hyperinsulinism may predispose the development of salt sensitive hypertension through an increase in renal sodium reabsorption. 3,28 Moreover, in response to high salt intake, salt sensitive hypertensives present alterations in both the sympathetic nervous and the renin-angiotensin systems 29 which may promote vasoconstriction and decreased muscle blood flow leading to insulin resistance. In this sense, Baron et al 30 demonstrated that insulin sensitivity is related to muscular blood flow increase induced by insulin itself.…”
Section: Discussionmentioning
confidence: 99%